2015
DOI: 10.3892/or.2015.4492
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine inhibits the proliferation of bladder cancer cells via reversal of the aberrant hypermethylation of the hepaCAM gene

Abstract: Hepatocyte cell adhesion molecule (hepaCAM), a tumor-suppressor gene, is rarely expressed in bladder carcinoma. However, little is known concerning the mechanisms of low hepaCAM expression in bladder cancer. Abnormal hypermethylation in the promoter plays a crucial role in cancer by silencing tumor-suppressor genes, which is catalyzed by DNA methyltransferases (DNMTs). In the present study, a total of 31 bladder cancer and 22 adjacent tissues were assessed by immunohistochemistry to detect DNMT3A/3B and hepaCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…DNMT1, the most abundant methyltransferase in mammals, is involved in maintaining established DNA methylation which was triggered by DNMT3a and DNMT3b (Baylin and Herman, 2000;Eng et al, 2000). 5-aza-2'-deoxycytidine (5-AzadC) is an inhibitor of DNA methylation, it blocks enzymatic activity of the three methyltransferase (Lindner et al, 2013;Wang et al, 2016a). Accumulating evidence have implied that DNA methylation occurs in genes involved in fibroblast activation and fibrogenesis (Bian et al, 2014;Tao et al, 2014), and up-regulation of DNMTs have also confirmed in fibrotic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1, the most abundant methyltransferase in mammals, is involved in maintaining established DNA methylation which was triggered by DNMT3a and DNMT3b (Baylin and Herman, 2000;Eng et al, 2000). 5-aza-2'-deoxycytidine (5-AzadC) is an inhibitor of DNA methylation, it blocks enzymatic activity of the three methyltransferase (Lindner et al, 2013;Wang et al, 2016a). Accumulating evidence have implied that DNA methylation occurs in genes involved in fibroblast activation and fibrogenesis (Bian et al, 2014;Tao et al, 2014), and up-regulation of DNMTs have also confirmed in fibrotic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…HepaCAM reexpressed in renal carcinoma and breast cancer cells inhibited cell proliferation and colony formation, and induced cell senescence5678. In bladder cancer, it has been found that the expression of hepaCAM is silenced by hypermethylation, and reversal of hypermethylation by inhibiting DNA methyltransferases led to the reexpression of hepaCAM and reduction in cell growth91011. Further, hepaCAM expression has been shown to induce differentiation of glioblastoma cells12.…”
mentioning
confidence: 99%
“…On the other hand, in an analysis of formalin-fixed paraffin-embedded primary BC tissue samples, methylation of SFRP5 was associated with recurrence and CACNA1G was associated with BC progression [ 55 ]. Moreover, DNMTs were shown to be overexpressed in BC, representing an attractive target for anti-cancer therapies [ 56 ].…”
Section: Dna Methylationmentioning
confidence: 99%